Issues and challenges facing Islamic financial institutions in Malaysia - Ishak, Mohd. Shuhaimi; Abdullah @ Chuah Hock Leng, Osman; Abdul Razak, Dzuljastri (UPM Press, 2013)
The issue of riba or usury has long been a problem for Muslims. The establishment of Islamic financial institutions is a major step in addressing this predicament, as Islamic finance has been characterized as a body to remove exploitation and injustice. The concepts of Islamic finance were initially discussed in the mid 1940s; however, further details were only revealed and then practiced in the late 1960s. The Pilgrims Management and Fund Board of Malaysia (TPMFB) established in 1962 was the earliest Islamic financial institution set up to cater for the pilgrims in Malaysia. This was followed by Bank Islam Malaysia Berhad (BIMB) in 1983, which marked the beginning of commercial financial institutions offering Islamic products and services to consumers. This paper evaluates the issues, challenges and prospect of this emerging industry, and ends with suggestions and recommendations on how they can be addressed for Muslims to go forward in the field of financing.